Moderation (Wasatiyyah) as positive action in the Risale-I Nur - Akhmetova, Elmira (2017)
This paper discusses the ideas of a Turkish scholar, Bediuzzaman Said Nursi on the importance of wasatiyyah (moderation) in creating a better world for entire humanity.